Toroidal dipole excitation in cylindrically arranged dogbone metallic inclusions. Issue 10 (7th December 2021) - Sarin, V. P.; Vinesh, P. V.; Manoj, M.; Aanandan, C. K.; Mohanan, P.; Vasudevan, K.
Abstract: A significant excitation of toroidal moments in cylindrically arranged dogbone metallic inclusions is validated and presented in this paper. The antiparallel poloidal currents excited on the front and back faces of the proposed cylindrical dogbone inclusions create strong magnetic field confinement at the center generating intense toroidal moments on the structure. The significant excitation of toroidal dipole moment causes an improvement in the scattering cross-section from the resonant system. The resonant mechanism is analyzed using the multipole scattering theory, and we used the scattering measurement techniques to characterize the structure experimentally in the microwave regime.